Pengembangan Potensi Pantai Lovina Sebagai Ekowisata Pesisir Di Desa Kalibukbuk, Kabupaten Buleleng, Bali - Purwita, Putu Udiani; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA; Vol 6 No 1 (2018): VOL 6, NO 1 (2018): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2018)
The gap in tourism development in the province of  Bali is still very large that is between the northern part of Bali and southern Bali. the right tourism development on the coast of North Bali is ecotourism, an area that has the potential to be developed inti an ecotourism attraction is Lovina Beach. The purpose of this study is to determine the potential of resources and to know the development of resources that support coastal ecotourism in Lovina Beach. The research method used is comparative descriptive method. Where in this method will be compared between ecotourism principles such as principles of nature and culture conservation, principles of community participation, economic principles, education principles, and tourism principleswith existing tourism resources at Lovina Beach to obtain ecotourism development plan in Lovina Beach. The main result of this research is there are four tourism resources that can be developed into ecotourism at Lovina Beach , including attraction of dolphin, marine park ecosystem, “genjek” performance and Lovina Festival. Ecotourism product development refers to several ecotourism criteria, including the principles of nature and culture conservation, principles of community participation, economic principles, education principles, and tourism principles. As for suggestion that can be given to the local community is to contribute more actively in preserving marine ecosystems, for government and investors involved are expected to give more attention to conservation of ecological environment and marine park in Lovina Beach as an ecotourism product.   Keywords : Development, Coastal Ecotourism, Resources, Lovina Beach